Buying versus renting: On the environmental friendliness of item-sharing. (October 2020) - Behrend, Moritz
Highlights: Environmental impact comparison of sales-based and sharing-based business models. Emission balancing of producing less items against additional item transports. Development of a framework to compare traditional and novel business models. Free-floating sharing with crowdshipping has the lowest environmental impact. Wear and limited lifetimes of items significantly impact buy-or-rent decisions. Abstract: Item-sharing is a concept of the sharing economy where items such as tools or leisure equipment are made available to a community and are accessed need-based. This allows to serve demand with a few highly utilized items, which is why item-sharing connotes resource efficiency and environmental friendliness. However, a shared use also necessitates to (repeatedly) transport single items between consecutive consumers. This kind of transports are relatively inefficient and may significantly affect the environmental efficiency of item-sharing. We investigate to what extent a few shared items allow to serve demand and under which circumstances the environmental benefit of providing fewer items is larger than the negative effects of a higher transportation effort. To this end, we develop a business model comparison framework to analyze and compare alternative ways of serving requests regarding the degree of request fulfillment and the emissions that are released during item production and transport. Our comparison includes variants of a traditional sales-based approach and two types of item-sharing in which items are either exchanged via stations or transferred directly from one consumer to another. We show by simulation studies for a large metropolitan area that item-sharing with direct transfers has a great emissions-cutting potential and that it becomes even more efficient if item exchanges are facilitated through so-called crowdshippers who offer to conduct transports on trips they would make anyway. The low environmental impact of item-sharing is further demonstrated in experiments with different requesting behaviors, various emission rates, and item replacements due to wear and obsolescence.